Relato de atividades de ensino utilizando o Cubiu planta regional amazônica para o ensino de tópicos de ciências e biologia - Sousa, Leandro Silva e (Brasil, 2022)
This work was developed to present the cubiu plant. It is a regional Amazon plant belonging to the family Solanaceae, native and domesticated in the Amazon. Its fruit is appreciated for its similar taste to an unprecedented combination of citrus, but is poorly cultivated. Cubiu is a shrub that grows on the latosol and the sandy loam soil of the low humid tropics of the Amazon. The objective of the work was to provide relevant information for teaching science and biology using the general benefiting aspects of cubiu. The research was developed during the supervised stage II and during the top vegetable morphology classes where there was the opportunity of applying a project that would provide the relevant information for teaching science and biology using a regional Amazon plant. With lectures it was divulged the knowledge of cubiu that were presented in lectures using the whiteboard and data show. Interactive classes with games: They were developed with the use of a game. Validation of Activities by undergraduate students 6th period: As a way of verifying the relevance of the project, undergraduate students participated by attending and evaluating the classes that were applied to elementary education. In order to observe the previous and final knowledge about a questionnaire was applied with questions involving the economic, regional, botanical and nutritional importance of the fruit. This work presented the botanical, nutritional and regional characteristics of Solanum sessiliflorum.